How to access and administer the selection interview? - Wong, Huey Siew (2010)
It is common that many employers have no idea as to what to do when Orang Kurang Upaya (OKU) candidates come for job interviews. As a result, they just simply entertained them and always end up with unfavorable outcome. Perhaps, some employers are really interested to hire OKU staff but they are not able to materialize this due to the psychological barriers as well as lacking experience in handling OKU applicants. On the other hand, OKU candidates also wish to secure jobs but are always unsuccessful because they are not performing during the interview. Therefore, both parties, employers and OKU alike, need proper guidance. They need more information on how to make use of available tools to assess the capabilities and the abilities of OKU candidates. The problem is that there are so many tools such as application forms, CV, psychological tests, interviews, reference letters etc. what and which tools are more practical and reliable as well as valid? Therefore, this paper will discuss with you concerning how employers can use the interview as an effective predictor of OKU candidates’ performance. This paper will also discuss how employers can conduct interview sessions effectively and what are needed in order to be prepared for interviewing OKU candidates. Then, it will also provide some useful guidelines to OKU candidates on interview matters. (Introduction by author)